The combined effect of serum cystatin C and dyslipidemia on hypertension in a large health check-up population in China. (17th November 2019) - Ma, Jun; Wu, Zewei; Zha, Xiaojuan; Zhu, Xinying; Li, Wenbo; Jiang, Mingfei; Wang, Shuyi; Wu, Shouzhi; Wen, Yufeng
ABSTRACT: OBJECTIVE : Some studies have reported that both serum cystatin C (Cys C) and dyslipidemia are independently associated with hypertension. However, the combined effect of the two factors is still unknown. The present study was aimed at investigating the effect of Cys C combined with dyslipidemia on hypertension in a large health check-up population in China. METHODS : A total of 203 233 health check-up subjects from January 2011 to July 2016 were recruited into this cross-sectional study. A multivariate logistic regression model was used to evaluate the combined effect of Cys C and dyslipidemia on hypertension. RESULTS : In univariate analysis, Cys C, high-density lipoprotein cholesterol, low-density lipoprotein, total cholesterol, and triglycerides were independently correlated with hypertension (p < 0.001). A concentration-dependent combined effect of serum Cys C and dyslipidemia on hypertension was observed in multivariate regression analysis. When compared with Cys C of <0.82 mg/L, the risk of hypertension in Cys C of <0.82 mg/L with dyslipidemia, Cys C of 0.82–0.94 mg/L with dyslipidemia, Cys C of 0.94–1.08 mg/L with dyslipidemia, and Cys C of ≥1.08 mg/L with dyslipidemia was increased 1.946 (95% confidence interval [CI]: 1.827–2.074), 1.973 (95% CI: 1.864–2.088), 2.047 (95% CI: 1.941–2.158), and 2.038 (95% CI: 1.937–2.143) folds, respectively, after adjustment. CONCLUSION : There was an association between hypertension and the combined effect of Cys C with dyslipidemia.